Synthesis of Ti4+ modified COF-based polymer for efficient enrichment of phosphopeptides in colorectal cancer serum - Jiang, Bengui; Cai, Yannan; Cao, Zhenzhen; Hua, Shuwen; Zhou, Xinyue; Meng, Luyan; Ding, Chuan-Fan; Yan, Yinghua; Cai, Ting (Microchemical journal, 2024)
[Display omitted] •COF-PA-Ti4+ with good hydrophilicity and abundant titanium ions was prepared by a facile synthesis method.•Radical polymerization on COF enables abundant modification sites, enhancing the enrichment properties.•The ability of COF-PA-Ti4+ to enrich phosphopeptides in serum provides a new method for rapid diagnosis of CRC. In this study, we propose a Ti4+ modified COF-based polymers (COF-PA-Ti4+) with a facile synthesis method for efficient enrichment of phosphopeptides in colorectal cancer serum. Thanks to the abundant modification sites provided by radical polymerization on COF, as well as the excellent hydrophilicity of vinyl phosphate and the strong chelating ability of Ti4+, COF-PA-Ti4+ have superior performance on phosphopeptides enrichment. Employing COF-PA-Ti4+ as the enrichment material, the detection method exhibits high selectivity (1:1000), low detection limit (low as 0.005 fmol μL−1), high size-exclusion effect (1:10,000), excellent reusability (10 cycles), good recovery (98.7 ± 0.6 %), and loading capacity (50 mg g−1), with analysis performed via MALDI-TOF MS. Most importantly, after enriching phosphopeptides from the serum of colorectal cancer (CRC) patients and healthy individuals by COF-PA-Ti4+, we discovered significant differences in the phosphopeptides between the two groups, validating the feasibility of this approach. Taken together, these results confirm that COF-PA-Ti4+ has an outstanding contribution to the precise capture of phosphopeptides and provides an innovative approach for rapid diagnosis of early CRC.